Atividade anti-helmíntica do DL-Tetramisole e do Thiabendazole em uma estirpe de Trichostrongylus colubriformis resistente ao Levamisole - Santiago, Marco Aurélio Miranda; Costa, Ubiratã Cereser da; Benevenga, Sérgio Fauque (Revista do Centro de Ciências Rurais, 2008)
Estudos efetuados sobre uma estirpe de Trichostrongylus colubriformis de ovinos, resistente ao levamisole, em uma fazenda situada no município de Itaqui, RS, revelaram que toda população desses vermes é resistente à dose recomendada de levamisole. Utilizando-se infestações puras, foi verificado que doses de 7,5 mg/kg de levamisole e 12,5 mg/kg de dl-tetramisole são inócuas contra esta estirpe, enquanto que 15,0 mg/kg de levamisole elimina apenas 45,5% desses helmintos. Entretanto, 44,0 mg/kg de thiabendazole é 100% eficiente contra esses parasitos.AbstractIt was verified a levamisole resistant strain of Trichostrongylus colubriformis parasitizing the sheep of a farm located at Itaqui county, RS. Field worm population presented resistance to the usual dose of the anthelmintic. The Trichostrongylus colubriformis larvae of these strain was obtained in pure culture. Experimental infection with pure culture were carried out. Experimentally infected lambs were treated with levamisole, dl-tetramisole and thiabendazole. Levamisole had no anthelmintic effect at a level of 7,5mg/kg, but 45,5% of the worms were eliminated at a level of 15,0 mg/kg. Racemic tetramisole (12,5 mg/kg) has no anthelmintic activity; notwithstanding thiabendazole (44,0 mg/kg) is 100% active against the resistant worms.